Analisis Kesulitan Mahasiswa Baru Pendidikan Matematika Dalam Mengerjakan Soal Pisa - Hendroanto, Aan (Penerbit STKIP PGRI Bangkalan, 2018)
One of the most important contributing factor to PISA result in Indonesia is teachers who have direct contact with students. Therefore, teacher trainings in higher education must prepare their students so that they have good ability to understand and solve PISA test. In order to do it, a thorough study of studentsâ difficulties is needed so that an effective method can be chosen to support them. The current study aims to investigate students in mathematics education program to determine their difficulties in solving PISAâs mathematics problem. This is a descriptive qualitative research involving 20 students of mathematics education, Universitas Ahmad Dahlan. Data were collected by using PISA instruments to determined studentsâ difficulties and was quantitatively and qualitatively analyzed by based on PISAâs framework. The result shows that students shows a good performance on problems with interpretation process, but in the formulation process and employment process, they are still experiencing many difficulties. Good performance is also found in problems with individual and social contexts. However, on problems related to work and scientific context, students do not perform well enough in understanding and solving the problems